Ocular Albinism Type 1 Regulates Deltamethrin Tolerance in Lymantria dispar and Drosophila melanogaster - Sun, Lili; Liu, Peng; Zhang, Chenshu; Du, Hui; Wang, Zhiying; Moural, Timothy W.; Zhu, Fang; Cao, Chuanwang (Frontiers in Physiology, 2019)
The ocular albinism type 1 (OA1), a pigment cell-specific integral membrane glycoprotein, is a member of the G-protein-coupled receptor (GPCR) superfamily that binds to heterotrimeric G proteins in mammalian cells. We aimed to characterize the physiological functions of an insect OA1 in regulation of insecticide stress tolerance. In present study, we investigated the roles of LdOA1 in response to deltamethrin stresses in both Lymantria dispar and Drosophila melanogaster. LdOA1 was expressed at the lowest level during the 4th instar stage, while LdOA1 was significantly upregulated in the 5th instar and male stages. Knockdown of LdOA1 by injecting dsRNA of LdOA1 into gypsy moth larvae, caused 4.80-fold higher mortality than the control larvae microinjected with dsRNA of GFP under deltamethrin stress. Nine out of 11 L. dispar CYP genes were significantly downregulated under deltamethrin stress in LdOA1 silenced larva as compared to control larva. Moreover, the LdOA1 gene was successfully overexpressed into D. melanogaster using transgenic technique. The deltamethrin contact assay showed that the LdOA1 overexpression flies significantly enhanced the tolerance to deltamethrin compared to the control flies. Furthermore, the downstream Drosophila CYP genes were upregulated in the LdOA1 overexpression flies, suggesting LdOA1 may play a master switch role in P450-mediated metabolic detoxification. It is the first time to report that an insect OA1 gene plays a role in tolerance to insecticide stress and in regulation of downstream cytochrome P450 expression. These results contribute to the future development of novel insecticides targeting insect GPCRs.